Pessoas com deficiência e concurso público - Maia, Maurício (2014)
The Federal Constitution, which the main vectors of interpretation are human dignity and equality, recognizes people with disabilities as a vulnerable group, that needs special protection of the law, in order to allow them the full and effective inclusion in society at equal opportunities in comparison to other people. Currently, due to the incorporation of the UN s Convention on the Rights of Persons with Disabilities, with equivalence of constitutional amendment, the term disability has a social character, and not only a medical character, indicating an obligation for the State to take measures with the aim of eliminating or reducing barriers in the environment and in the society, providing inclusion. That way, it is established in Article 37, VIII, of the Constitution, an affirmative action that requires the reservation of a percentage of public offices and public jobs for people with disabilities, under the law. The Law, in turn, established a reservation of up to 20% (twenty percent) of vacancies in dispute in public contests, as well as, regarding to State companies, whose staff is regulated by the labour regime, is established that those companies must reserve percentage of their jobs for persons with disabilities. For implementation of affirmative action and its compatibility with all Brazilian constitutional system, however, is not enough the simple reservation of vacancies in public contests, but it is necessary to establish several parameters and procedures in the realization of public contests, from the preparation of bidding documents, through the adaptation of tests and places of examinations, and mechanisms of classification and appointment of successful candidates, as well as must be established procedures of adaptation and appropriate monitoring of probation (or trial) period. The right to have places reserved in public service may be required administratively and judicially, even as the levying of the obligation of Administration to promote the inclusion, and may result in the liability of the State and of the public officials who acted inappropriately